Pendidikan Islam Transformatif untuk Ekonomi Sirkular: Studi Kasus Pengelolaan Sampah Berbasis Pirolisis di Pedesaan Pasuruan, Indonesia - Sofiyulloh; Enik Sulistyowati (Tarbawi : Jurnal Studi Pendidikan Islami, 2025)
Purpose: This study aims to explain the process of transformative Islamic education in community-based plastic waste management through a combination of pyrolysis technology and biomass in Manikrejo Village, Pasuruan Regency, and to analyze its impact on changing paradigms, community independence, and the creation of circular economic value.Design/methodology/approach: This research employs a qualitative case study approach with data collection through participant observation, in-depth interviews with 35 informants consisting of religious leaders, village officials, waste management group administrators, training participants, and sub-district government representatives, as well as documentation during the community service program from June to December 2025. Data analysis uses an interactive model and triangulation to ensure validity.Findings: The results reveal three main stages in transformative Islamic education through this program. First, internalization of Islamic values such as cleanliness, moral responsibility, and mutual cooperation becomes the motivational foundation driving community participation, with religious figures acting as catalysts for behavioral change. Second, the implementation of learning-by-doing methods with tiered mentorship successfully transforms residents from passive recipients into competent technology operators, with 90% of participants able to operate pyrolysis reactors independently. Third, a fundamental paradigm shift occurs where plastic waste is no longer viewed as an "environmental burden" but as a "potential raw material" with economic and functional value. The program produces measurable impacts: every 5 kg of plastic waste is converted into 3.5 liters of pyrolysis oil and 1 kg of biochar, creating environmental, economic, and social benefits simultaneously.Research limitations/implications: This study is limited to one village context in Pasuruan Regency, East Java. However, it provides valuable insights for the development of transformative Islamic education models in non-formal and community-based settings, and offers an alternative approach for Islamic educational institutions facing the challenge of integrating spiritual values with appropriate technology and environmental sustainability.Originality/value: This research contributes to the literature on transformative Islamic education by documenting a proven community-based educational approach that integrates spiritual values, local wisdom, and circular economy principles. The learning-by-doing method combined with tiered mentorship represents a modern adaptation of the sanad system in Islamic scholarly tradition, offering a replicable framework for similar programs in other rural contexts in Indonesia and other developing countries.